2019
DOI: 10.1007/s12325-019-01096-0
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus on Clinical Use of an Orally Administered Dexketoprofen Plus Tramadol Fixed-Dose Combination in Moderate-To-Severe Acute Pain: A Delphi Study

Abstract: IntroductionIn 2016, the orally administered fixed-dose combination of dexketoprofen 25 mg and tramadol 75 mg (DKP/TRAM FDC) was approved in Europe for short-term treatment of moderate-to-severe acute pain, an indication that encompasses a wide range of post-operative and non-surgical painful conditions. This has suggested the necessity to have a clearer indication on its clinical use, with the support of expert pain clinicians, working in different medical specialities, and reinforced by the data present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Owing to its pharmacological profile, the oral fixed-dose combination tramadol/dexketoprofen 75/25 mg (TRAM/DKP) may provide pain control in acute exacerbations of LBP and be suitable for mixed types of pain including non-specific LBP where nociceptive and neuropathic mechanisms are involved at both local and central levels 21 . While some evidence on the clinical efficacy of TRAM/DKP in acute LBP had been reported 22 , further evaluation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its pharmacological profile, the oral fixed-dose combination tramadol/dexketoprofen 75/25 mg (TRAM/DKP) may provide pain control in acute exacerbations of LBP and be suitable for mixed types of pain including non-specific LBP where nociceptive and neuropathic mechanisms are involved at both local and central levels 21 . While some evidence on the clinical efficacy of TRAM/DKP in acute LBP had been reported 22 , further evaluation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…This study used a modified Delphi technique to develop consensus recommendations based on experts' collective experience and knowledge with medications in older patients in Africa. This method appears to be a reasonable scientific approach in the absence of randomized controlled trials of medications among older persons in Africa . In this study, the Delphi technique was modified by the use of electronic mail instead of the face‐to‐face and conference calls applied in the development of the 2015 AGS‐Beers Criteria .…”
Section: Methodsmentioning
confidence: 99%
“…The Delphi technique is a flexible, robust, and reliable method widely used to obtain a consensus of opinions among experts on many clinical issues including the development/adaptation of guidelines . It seeks to develop consensus recommendations based on experts' collective experience and knowledge with a clinical problem . Although experts' consensus ranks the lowest in the grades of evidence for clinical guidance and stands the risk of presenting biased views of evidence, in situations where there are evidence gaps, it is considered a dependable source of clinical evidence .…”
Section: Introductionmentioning
confidence: 99%
“…Further studies comparing this FDC to other clinically available COX inhibitor/opioid receptor agonist combinations as well as long-term and real-world studies are expected to yield important information about painful conditions that will benefit most from treatment with this latest analgesic combination. Until this evidence becomes available, consensus statements have been recently developed to provide guidance for its use and support clinicians to identify both patient populations and clinical settings for whom this combination may appear an appropriate and valuable treatment option [ 66 ]. The recent Delphi study suggested that, in day-case surgery, tramadol/dexketoprofen could provide effective and rapid pain management, enabling patients to return more quickly to their normal daily activities, in major abdominal and orthopaedic surgery, tramadol/dexketoprofen has proved to be an effective treatment of moderate-to-severe acute post-operative pain.…”
Section: Fixed Dose Cox-inhibitor/opioid Receptor Agonist Combinationmentioning
confidence: 99%
“…Of note, it has been proposed as suitable option for mixed types of pain, arising from different body structures (joints, muscles, ligaments, etc.) such as acute articular pain or non-specific low back pain (Table 3 ) [ 66 ].…”
Section: Fixed Dose Cox-inhibitor/opioid Receptor Agonist Combinationmentioning
confidence: 99%